Analysis of the Use of a Zener Diode as a Voltage Regulator in a Zener Follower Circuit - Ali, Mukti; Khuzaimah, Andi Ulfah; Ikbal, Muh. Syihab (Al-Khazini, 2026)
This study aims to analyze the performance of the Zener Follower circuit as a linear voltage regulator under varying input voltage (Vin) conditions, using a configuration where the load resistor (RL) is greater than the series resistor (RS). The experiment was conducted at the Electronics Laboratory of Universitas Islam Negeri Alauddin Makassar using basic components such as a Zener diode, an NPN transistor, and two resistors. The observed variables included Vin, Zener voltage (Vz), output voltage (Vout), and source current (Is). Measurement results showed that Vout remained relatively stable, with only a slight drop due to the base-emitter voltage (VBE) of the transistor. The deviation between the actual Vout and the theoretical value (Vz – VBE) ranged from 1% to 7%, indicating that the system maintained acceptable stability within laboratory experiment tolerances. The source current increased proportionally with the Vin, confirming that the system operates according to basic electrical principles. These findings suggest that the Zener Follower configuration is effective as a simple voltage regulator in educational applications and laboratory practice. The addition of features such as output filter capacitors or a Darlington configuration is recommended for improved accuracy and system stability in future studies